EDUCATIONAL LAW POLITICS IN THE PERSPECTIVE OF TRANSENDENTAL LAW - Rezi; Istiyawati Rahayu (International Journal of Law and Legal Ethics, 2021)
Education in a general sense is a form of learning in which the knowledge, skills and habits of a group of people are transferred from one generation to the next through teaching, training, research or simply through self-taught. Our constitution has guaranteed the Right to Education which has been stated in the 1945 Constitution Article 31 as a result of the last amendment. The presence of a constitution that is nuanced in human rights will provide protection to citizens and give responsibility to the state in its fulfillment or implementation. Indonesia's education policy has been aligned with the transcendental context, namely making policies that are sourced from Revelation or the text of the Koran and then poured into the constitution and laws without having to use the language of Revelation. Even though the implementation level there are still many shortcomings. The realization of the fulfillment of the right to education in Indonesia in general can be categorized as minimal. Especially on the following four indicators: (i) Availability (availability), (ii) Accessibility (accessibility) (iii) Acceptability (acceptance or acceptable) and (iv) Adaptability (suitability).